The Proses pembuatan biji plastik menggunakan mesin extruder pelletzing plastic - Muhammad Fajar Sidik, Fajar (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2021)
The problem of garbage is a problem that often occurs, both in the home environment, in the community, on a small scale and on a wider scale. There are many kinds of waste / waste that are around our environment, in general, such as organic waste and non-organic waste. Plastic is one of the materials that is widely used for the manufacture of household, automotive and so on. One of the alternatives for handling plastic waste is to recycle it. The extruder machine is a plastic change process (LDPE) that has been crushed and then extruded (changing from solid to liquid). This change process goes through various heat stages, the function of the extrusion machine is to treat plastic waste. Through several stages, namely the hopper, barrel, screw lip, cooling tub, dryer fan, cutting machine, filter 2, the calculation results of the heat transfer in a barrel with a temperature of 240-268 ℃ can be concluded, the heat rate in the barrel is 28100.8 h. / s and the amount of heat in the barrel of 218700 j. so as to produce a good and appropriate plastic seed product. Keywords: plastic waste, plastic pellets. exstruder.